Unteilbar und untrennbar? Die Verhandlungen zwischen Cisleithanien und Ungarn zum gescheiterten Wirtschaftsausgleich 1897 - Schmied-Kowarzik, Anatol (Studien Verlag, 2010)
Focussing on the necessary renewal of the economic compromise of Cisleithania and Hungary in 1897, the beginning of the great "Crisis of the Dualism of the Habsburg Monarchy" will be examined. This work is based on the archives in Vienna and Budapest of the ministers of finances and the archives of the primeministers (ÖStA.., HHStA., MOL.) as well as the protocolls of both parliaments. In October 1895 the new prime minister of Cisleithania, Badeni, started the negotiations with Hungary for the renewal of the economic compromise. This new compromise should have been finished in 1896, one year earlier than necessary to be a signal of strength and unity inside and outside the monarchy. In August 1896 this plan of an early compromise had to be dropped due to early elections of the Hungarian parliament. In May 1897 the renewal of the compromise again had to be postponed for one year. Cisleithania and Hungary couldn't find an agreement about the partition of the common expense between them (quota). Only the old compromise of 1887 could be prolonged for 1898. This so called Ausgleichsprovisorium (provisional compromise) was approved by the Hungarian parliament very quickly. In Cisleithania however it was facing the obstruction of the German parties of the elected chamber of parliament. The Germans wanted to force the Government to revoke the so called Badenian languages decrees for Bohemia and Moravia. These set the Czech language beside German even in the inner administration of these "crown lands" (provinces). The German fight against the government was concentrated on the Ausgleichsprovisorium due to the fact, that this was the only law, the government couldn't issue by an emergency decree; the Hungarian law of the constitutional compromise of 1867 didn't accept emergency decrees instead of laws on common issues. With this obstruction the German parties risked continuation of custom's union with Hungary and placed its future completely in Hungarian hands; they set their national above their economic interests. In November 1897 Badeni had to be dismissed. The German obstruction had successfully prevented the provisional compromise; the legal base of 1867 of the economic union was cast aside. Only by independent Cisleithanian and Hungarian laws could the unity be saved. Instead of a sign of strength and health, Austria-Hungary demonstrated its weakness and its inner strife.